Impact of organic acids supplementation to hardwood spent sulfite liquor as substrate for the selection of polyhydroxyalkanoates-producing organisms - Queirós, Diogo (2019)
This work was developed within the scope of the project CICECO-Aveiro Institute of Materials (Ref. FCT UID/CTM/50011/2013) and REQUIMTE (PEst-C/EQB/LA0006/2013), financed by national funds through the FCT/MEC and when appropriate co–financed by FEDER under the PT2020 Partnership Agreement.